FACTORS ASSOCIATED WITH LOW ACHIEVEMENT IN POLIO IMMUNIZATION - Reni Fitria; Sri Fawziyah; Erma Erfiana (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Background of the research: The Ministry of Health Republic of Indonesia has been implementing Polio Immunization (PIN) 2016 simultaneously in Indonesia since 8 to 15 March 2016. Overall, the result of implementation PIN polio at Dharmasraya regency in 2016 has reached about 93.15%. While the lowest scored was reached by Tiumang PHC 75.76%. The purpose of this research is to determine the factors associating on the low of reaching polio immunization in March 2016 at community health centers (Puskesmas) Tiumang Dharmasraya 2016. Methods: using descriptive analytic with Cross-Sectional Study research design. The number of samples is 94 people with accidental sampling technique. Where the research was conducted in Puskemas Tiumang, Dharmasraya. Data were collected using a questionnaire then processed by SPSS software. The result of the study is presented in the form of distribution frequency and chi-square test. Result: The study showed that almost half of 42 respondent were knowledgeable (44.7%), negative (45.7%), and the lowest (3.2%) in no act category. Furthermore, almost half is supported by negative family (30.9%). The result of the statistical test found that (p-value=0.093), there is no significant relationship between knowledge and polio immunization. Moreover, there is no significant relationship between attitudes toward immunization values (p-value=0.082), there is no significant relationship between the cadres roles and polio immunization (p-value=0.591). However, only family support that can reach the significant relationship toward immunization (p-values= 0.005). Discussions: it is hoped that mothers concern about their children‟s health to be kept and those who have not been motivated yet to visit with their children getting immunization polio.Key Word: Knowledge, Behavior, Achieviement, Polio